(untitled) (Research, Society and Development, 2020)
The routine of the military police has several factors that can contribute to the appearance of musculoskeletal injuries, with low back pain being the most prominent in this professional context. The aim of the present study is to characterize national research, published in the last 20 years, on musculoskeletal injuries and low back pain in military police officers. The content analysis was done through the technique of frequency analysis by specific software, and by the process of coding and categorical identification. For this, a literature survey was carried out in 3 directories, namely: SciELO, Lilacs and Capes Periódicos, and in the Dissertations Bank of the Post-Graduate Program in Public Security / UFPA, using specific descriptors for the selection of articles. The results showed that the survey resulted in 7 articles, both found in the CAPES directory, which met the inclusion criteria for this literature review. As for the results, it was noted that in the coding process two categories of analysis emerged, musculoskeletal injuries and low back pain in military police. In the frequency study there was a higher frequency of some terms such as: "work" (f = 17), "conditions" (f = 9), "injuries" (f = 9), "vest" (f = 8) and "fatigue" (f = 8). It is considered that the use of equipment, associated with the working conditions of the military police, poses a risk to them, in the short and long term. Thus, it is emphasized the need for further investigation of the theme, linked to risk factors that can promote the appearance of injuries.